PENGARUH KONSEP TRAVEL CAREER LADDER (TCL) TERHADAP ISLAMIC TOURISM DESTINASTION PADA WISATA RELIGI SUNAN AMPEL - Mei Santria (Perpustakaan Universitas Surabaya, 2019)
Abstract- Penelitian ini bertujuan untuk menguji konsep Travel Career Ladder (TCL) teori hierarki kebutuhan Maslow yang terdiri dari Selffullfilment needs, Self-esteem needs, Relationship needs, Safety/Security needs, Physiological needs terhadap Islamic Tourism Destination Sunan Ampel. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan metode Structural Equation Modelling (SEM) dengan software Partial Least Square (PLS) dengan melakukan evaluasi pada tahap Measurment dan Structural. Penelitian ini melibatkan 150 responden yang pernah mengunjungi destinasi wisata Islam Sunan Ampel. Kata kunci: Self-fullfilment needs, Self-esteem needs, Relationship needs, Safety/Security needs, Physiological needs. This research aims to test the concept of Travel Career Ladder (TCL) Maslow’s hierarchy of needs, which consist of Self-fullfilment needs, Selfesteem needs, Relationship needs, Safety/Security needs, Physiological needs influential to Islamic Tourism Destination in Sunan Ampel. This research use a quantitative approach using Structural Equation Modelling (SEM) method with Partial Least Square (PLS) software and do an evaluation on Measurment and Structural phase. The study involved 150 respondents whomever have stayed at the Islamic Tourism Destination in Sunan Ampel. Keywords: Self-fullfilment needs, Self-esteem needs, Relationship needs, Safety/Security needs, Physiological needs.